1996
DOI: 10.1159/000127126
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and Autonomous Mechanisms Underlying Thermoregulation in Cold Environment

Abstract: This review focuses on the central regulation of thermoregulatory responses with special attention to the participation of thyrotropin-releasing hormone (TRH) in both autonomous and endocrine responses to a cold environment. Besides a direct projection of TRH neurons from paraventricular nuclei (PVN) to the median eminence, and the subsequent activation of the thyroid axis, there are direct projections from the PVN to the autonomic preganglionic neurons controlling autonomous responses. These projections conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 47 publications
(60 reference statements)
1
58
0
5
Order By: Relevance
“…By contrast, within the first 30 min of cold exposure, core body temperatures in mutants declined significantly, and by the end of 2 h, their body temperatures were reduced by at least 3°C (two mice showed a reduction by 6°C). Because the hypothalamicpituitary-thyroid axis is involved intimately in thermoregulation (26), these data suggest that this axis in the Cpe fat/fat mice is deficient.…”
Section: Status Of the Hypothalamic-pituitary-thyroid Axis In The Cpementioning
confidence: 81%
See 1 more Smart Citation
“…By contrast, within the first 30 min of cold exposure, core body temperatures in mutants declined significantly, and by the end of 2 h, their body temperatures were reduced by at least 3°C (two mice showed a reduction by 6°C). Because the hypothalamicpituitary-thyroid axis is involved intimately in thermoregulation (26), these data suggest that this axis in the Cpe fat/fat mice is deficient.…”
Section: Status Of the Hypothalamic-pituitary-thyroid Axis In The Cpementioning
confidence: 81%
“…Cold exposure stimulates the hypothalamic-pituitary-thyroid axis strongly (26). In rats, cold temperatures increase TRH mRNA levels in the hypothalamic paraventricular nucleus (46), augment TRH release from the median eminence (47), stimulate TSH secretion from pituitary, and potentiate T 4 and T 3 contents in blood (48).…”
Section: Pro-trh Processing and Thermal Responses In Cpementioning
confidence: 99%
“…Geralmente, a produção de hormônios da tireoide respondem às mudanças na demanda termogênica, imposta pelas alterações crônicas na temperatura ambiente. Temperaturas baixas aumentam a atividade do eixo da tireoide dos animais (Arancibia et al, 1996). O plano nutricional utilizado influencia de forma significativa a produção de calor nos animais no estresse por frio, que é altamente correlacionada com o peso dos órgãos metabolicamente ativos das aves, como o fígado, Além das respostas fisiológicas, os animais podem expressar comportamentos específicos com o intuito de manter a temperatura corporal constante, em situações de estresse por frio, dentre as quais se destacam, o agrupamento dos animais para minimizar a superfície de exposição corporal, afastam-se de locais com incidência de ventos, buscam fontes de calor nos galpões, e, persistindo a queda na temperatura ambiente, de forma involuntária, o animal poderá aumentar a atividade do músculo esquelético (tremor), proporcionando uma maior produção de calor (Albuquerque et al, 2011).…”
Section: Respostas Fisiológicas E Comportamentais De Galinhas Poedeirunclassified
“…The pFE22 C-terminal peptide and its processed forms are increased in the PVN during suckling as a result of changes in proTRH processing (68). As an adaptive response to increase body temperature, cold exposure is also associated with increased expression of preproTRH in hypophysiotropic neurons and, in turn, increased secretion of TSH and a subsequent increase in thyroid hormone levels (72). In studies with the Cpe fat mouse, we demonstrated that the Cpe fat mutation might affect TRH biosynthesis and that it caused aberrant proTRH processing (38); this suggests that various products derived from proTRH can be independently regulated under altered physiological conditions.…”
Section: Figurementioning
confidence: 99%